Peran Organizational Citizenship Behavior (OCB) pada Pengaruh Penghargaan terhadap Turnover Intention Karyawan PT Madubaru Bantul Yogyakarta - Abdul Jalil; Faza Nur'aini; Candra Vionela Merdiana (Journal of Principles Management and Business, 2025)
This study aims to examine the negative and significant effect of Reward on Turnover Intention, and whether Organizational Citizenship Behavior (OCB) is able to mediate the relationship between these two variables at PT Madubaru. The study population consist of 352 permanent employees of PT Madubaru. The sample selection of 100 respondents was carried out using purposive sampling method. This study adopts a quantitative approach, and uses questionnaires filled out by respondents in printed form or hard file as the main source of primary data. Data analysis was carried out using IBM Statistics 25, instrument testing was carried out through CFA validity and reliability tests using Cronbach’s Alpha, direct and indirect regression test, t test, regression test using the Baron & Kenny approach, and the coefficient of determination test. This study found that Reward does not significantly affect Turnover Intention, and OCB does not mediate the effect of Reward on Turnover Intention of employees at PT Madubaru. Based on the research findings, PT Madubaru is advised to evaluate its reward system to better align with employee expectations, as well as encourage active participation in company activities to foster a sense of belonging and reduce turnover intention.